Annual catch of rainbow trout, Oncorhynchus mykiss (Actinopterygii, Salmoniformes, Salmonidae), in fishing grounds in the Czech Republic, related to stocking - Zdeněk Adámek; Luděk Šlapanský; Pavel Jurajda (Acta Ichthyologica et Piscatoria, 2025)
The rainbow trout, Oncorhynchus mykiss (Walbaum, 1792), is a popular species for Czech recreational fishing, both on trout fishing grounds and even some designated as non-trout waters if they have sufficient environmental quality. Rainbow trout are usually stocked using a “put-and-take” management approach, in which the majority of fish are caught and harvested during the fishing season. Rainbow trout stocking and return data in anglers’ catches were analyzed with respect to the time period between stocking and catch and the rates of return were evaluated. Two differently managed types of fishing grounds were taken into account—the non-trout and trout grounds. The study was conducted on five fishing grounds (four rivers) in the Czech Republic within 2007–2020. The average proportion of stocked rainbow trout caught during the first two weeks after release on non-trout fishing ground is 92.3%, significantly (P < 0.001) higher than the 64.1% taken from designated trout grounds. On the trout fishing grounds, rainbow trout tend to be caught more evenly throughout the fishing season. Mean total individual return rates ranged between 36.8% and 53.4% in the non-trout fishing ground and between 29.8% and 68.4% in the trout fishing ground. The respective weight return rates were 47.7%–79.5% in the non-trout fishing ground and 34.4%–75.3% in the trout fishing ground with no significant differences in individual (P = 0.50) and weight-related (P = 0.19) returns. The vast majority of rainbow trout are caught and harvested shortly after being stocked. The proportion of stocked fish caught within two weeks of release in non-trout fishing grounds is significantly higher than in trout grounds. Stocked rainbow trout tend to be caught more evenly throughout the fishing season in trout fishing grounds due to lower angling pressure and legal restrictions (artificial flies and lures only). Both individual and weight returns for the entire year (season) were similar in non-trout and trout areas.